Measuring the environmental perception of university students using the 2-MEV scale: Validation with structural equation modeling and quantile regression (Research, Society and Development, 2021)
This article aimed to evaluate the 2-MEV model: Two Major Environmental Value, as a scale for measuring environmental attitudes of university students, related to the preservation and use of nature. To test the model, a sample of 241 university students was collected through a structured questionnaire, like a survey. The scale statements were validated using the confirmatory factor analysis technique, applying structural equation modeling, based on covariance. The scores for the two factors of the 2-MEV scale were mapped in orthogonal quadrants, following a quantile regression analysis to establish the linear conditional distribution of the two factors in each quartile. The results indicated a validation and consistency of the 2-MEV scale when applied to university students, indicating that they are mostly biocentric. Women and university students in health knowledge revealed more biocentric attitudes than the other categories. The analytical results of the quantile regressions, for the quartiles of 25% (lower quartile), 50% (median) and 75% (upper quartile), showed the coefficients of the utilization factor are negative, relating that an increase in its absolute value, causes a more anthropocentric attitude and a decrease in the biocentric attitude. It is recognized that the convenience sample of university students may be a limitation of the research. It is recommended that the sample be expanded and that longitudinal studies take place, including the insertion of environmental education programs. As the data and the model proved to be consistent, this article has its contribution to academic knowledge.